Фінансування видатків на соціальний захист громадян з державних цільових фондів - Насібова, Ольга Вікторівна (ТОВ "Фінтехальянс", 2017)
Розглянуто сучасний стан та тенденції фінансового забезпечення системи соціального захисту громадян за рахунок державних цільових фондів соціального спрямування в Україні. Здійснено оцінку видатків державних цільових фондів соціального спрямування за 2003–2015 роки та виявлено їх значення при формуванні стратегії розвитку соціальної політики держави. Визначено структуру та основні напрями фінансового забезпечення системи соціального захисту громадян за рахунок державних соціальних фондів в умовах соціально–економічних перетворень.

The current status and trends of financial provision system of social protection of citizens by the state trust funds in the social direction of Ukraine were reviewed. The estimation of the costs of the state trust funds in the social direction for the 2003–2015 years was implemented and also their importance in the formation of strategy of development of social policy was revealed. The structure and main directions of the financial providing of the social protection of citizen at the expense of the state social funds in conditions of socio–economic transformation were identified. It was proposed to increase the financial stability of the state social funds, by expanding of the access to productive employment. An urgent need is to find effective mechanisms of financial regulation in social spending and to manage the social risk. In order to form an integrated system of the state social insurance is necessary to realize the introduction of health insurance and the funded pillar of the pension system.
Funding of social protection of citizens with state funds
Keywords: фінансове забезпечення; соціальні виплати; видатки державних соціальних фондів; фонди соціального страхування; соціальний захист населення; соціальні видатки; соціальні послуги; financial support for social benefits; the cost of state social funds; social insurance funds; social protection; social spending; social services